Validation of Fiber Optic-Based Fabry-Perot Interferometer for Simultaneous Heart Rate and Pulse Pressure Measurements - Samartkit, Piyawat; Pullteap, Saroj; Seat, Han Cheng (IEEE sensors journal, 2021)
In this work, a fiber optic-based Fabry-Perot interferometer (FFPI) developed for simultaneous heart rate (HR) and pulse pressure (PP) measurement was investigated. Particularly, the FFPI was designed with simplicity in configuration for highly precise and non-invasive arterial distension measurement whose output was then demodulated via fringe counting to simultaneously obtain both HR and PP information through fringe pattern analysis and Kirchhoff-Love's plate theory, respectively. The sensitivity was then characterized by linear fitting of measured PP inducing a number of interference fringes, whose slope represented the FFPI sensitivity. Experiments were conducted both on a simulating device and healthy subjects, each measurement carried out at least 10 times. Obtained results demonstrated the FFPI sensitivity for PP measurement in both experiments to be ~1.916 mmHg/fringe. For HR measurements, an average difference of 1.24% was found when compared to a digital sphygmomanometer employed as reference. Analysis of the FFPI resolution revealed the impact of the fringe counting technique, interrogating wavelength, and sensing material properties on measurement accuracy. Consequently, the thickness of the transducing thin film was found to have the most impact on PP demodulation. Therefore, optimization of the aforementioned parameters could lead to the development of a more accurate FFPI for PP measurement.